Strategi Pemasaran Untuk Meningkatkan Daya Saing Bisnis Pasca Pandemi Covid-19 pada Toko Hijup Putri - Meisy Alfian Damayanti; Saida Zainurossalamia (MAMEN: Jurnal Manajemen, 2023)
The purpose of this study is to identify and plan marketing strategies that can increase the competitiveness of women's hijup shops after the covid-19 pandemic by using the SWOT analysis method. The phenomenon that exists is that women's hijup shops are facing quite fierce competition, marked by the increasing number of shops and online shops selling similar products. The SWOT analysis method is carried out by analyzing the IFAS (Internal Factors Analysis Summary) and EFAS (External Factors Analysis Summary) factors at the women's hijup shop to find out and assess what strengths, weaknesses, opportunities and threats are currently owned. Data collection techniques were obtained through observation, interviews and distributing questionnaires to the female hijup shop customers, totaling 40 respondents. From the results of data analysis, the total score of the IFAS and EFAS strengths factors has a total score of 3,442, weaknesses 2,720, opportunities 3,348, and threats 2.525. it is known that the difference in the total score of the strength and weakness factors is (+) 0.72, while the difference in the total score of the opportunity and threat factors is (+) 0.82. These results indicate that women's hijup shops are in quadrant I (Aggressive). The Hijup Putri shop is currently in a favorable situation, because the Hijup Putri shop has great strengths and opportunities, so it can take advantage of the opportunities that exist to the fullest. The strategy that must be implemented by Toko Hijup Putri is to support an Growth Oriented Strategy.